Hole-embedding block strategy to synthesize the NMOFs-NADH model: Selective capture and reduction of formaldehyde in aqueous and gaseous phases. Issue 6 (December 2022) - Li, Mengwen; Shen, Ao; Du, Man; Hao, Xiaohui; Du, Xiaoyu; Yuan, Jiaxin; Ma, Shufeng; Zhao, Yongwei; Hou, Lala; Li, Ziqi; Yang, Yunxu
Abstract: A new NMOFs-NADH model (UiO-66-NADH) had been designed and synthesized utilizing the hole-embedding block strategy for self-adaptive pore radius to FA, and could selectively capture and confined reductive remove of FA as a good donor of hydrogen proton in aqueous and gaseous phases. With the catalysis of tetra(carboxyphenyl)porphyrin iron (Ⅱ) (Fe-TCPP), UiO-66-NADH could selectively convert FA to methanol deeply and efficiently up to 98.6% within 40 min. In addition, the regeneration of UiO-66-NAD + /UiO-66-NADH was performed by g-C3 N4 via photocatalysis, and the recycled UiO-66-NADH still had high reduction activity after three cycles. While, a fixed bed reactor filled with UiO-66-NADH/Fe-TCPP mixture was employed for the selective absorption and removal of gaseous FA, also in the aqueous solution of some real samples. These results demonstrated that UiO-66-NADH/Fe-TCPP system had a great potential in environmental protection. The hole-embedding block strategy could be extended to related applications in air purification and environmental protection. Graphical Abstract: Hole-embedding block strategy to synthesize the NMOFs-NADH model: selective capture and reduction of formaldehyde in aqueous and gaseous phases. ga1 Highlights: A novel NMOFs-NADH (UiO-66-NADH) had been developed for the selective capture and confined reduction of formaldehyde. The reduction rate of FA was up to 98.6% by UiO-66-NADH, with the catalysis of Fe-TCPP. The recycling of UiO-66-NADH had been realized by the photocatalysis of g-C3 N4 . UiO-66-NADH/Fe-TCPP mixture was filled into a fixed bed reactor to capture the gaseous FA. UiO-66-NADH/Fe-TCPP had been employed for the practical removal of FA in real water samples.